(untitled) (American Journal of Technology and Applied Sciences, 2024)
The article is devoted to the essence and necessity of the introduction of digital technologies in the development of human capital, and the literature of economists was studied as part of the research. Also, the main directions of human capital development were investigated and a conclusion was formed at the end.